2006
DOI: 10.1103/physrevb.73.035103
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the momentum distributions of annihilating electron-positron pairs in solids

Abstract: Measuring the Doppler broadening of the positron annihilation radiation or the angular correlation between the two annihilation gamma quanta reflects the momentum distribution of electrons seen by positrons in the material. Vacancy-type defects in solids localize positrons and the measured spectra are sensitive to the detailed chemical and geometric environments of the defects. However, the measured information is indirect and when using it in defect identification comparisons with theoretically predicted spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 132 publications
(139 citation statements)
references
References 51 publications
5
120
0
1
Order By: Relevance
“…Besides the agreement with the 2CDFT, the results obtained with the conventional scheme also compare reasonably well with experiment. 18,23 First and foremost, the measured changes in the positron lifetime and in the relative changes in the core annihilation rate between the vacancy and bulk states are reproduced.…”
Section: A Theoretical Modelsmentioning
confidence: 86%
See 2 more Smart Citations
“…Besides the agreement with the 2CDFT, the results obtained with the conventional scheme also compare reasonably well with experiment. 18,23 First and foremost, the measured changes in the positron lifetime and in the relative changes in the core annihilation rate between the vacancy and bulk states are reproduced.…”
Section: A Theoretical Modelsmentioning
confidence: 86%
“…Our computational methods are described in more detail in Ref. 18 and, here, we will give only the main features. We perform electronic-structure calculations within the LDA.…”
Section: B Calculation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding negative (positive) charge is expected to lead to an additional inward 125201-2 (outward) relaxation, 11 while the Coulomb force of localized positrons is directed outward. 25 The exact charge state of defect complexes is often unknown in experiments, hence it is not safe to be assumed without further proof. On the other hand, only considering the positron-induced forces 31 leads to an overestimation of the outward relaxation.…”
Section: B Computationmentioning
confidence: 99%
“…Recent attempts, however, have shown that these limitations could in principle be overcome by careful modeling of positron annihilation parameters using ab initio calculations. [23][24][25] Despite this, to the best of our knowledge, a comprehensive theoretical study of positron annihilation in InN is still missing.…”
Section: Introductionmentioning
confidence: 99%